2020
DOI: 10.1136/jitc-2019-000189
|View full text |Cite
|
Sign up to set email alerts
|

CD200 promotes immunosuppression in the pancreatic tumor microenvironment

Abstract: BackgroundA significant challenge to overcome in pancreatic ductal adenocarcinoma (PDAC) is the profound systemic immunosuppression that renders this disease non-responsive to immunotherapy. Our supporting data provide evidence that CD200, a regulator of myeloid cell activity, is expressed in the PDAC microenvironment. Additionally, myeloid-derived suppressor cells (MDSC) isolated from patients with PDAC express elevated levels of the CD200 receptor (CD200R). Thus, we hypothesize that CD200 expression in the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 52 publications
2
70
0
Order By: Relevance
“…While stromal cells express both CD200 and CD200R, future work is underway to more specifically define the immune cell populations that express each protein. CD200R is principally expressed on immune cells of monocyte-macrophage lineage, with an emphasis on myeloid-derived suppressor cells (MDSCs) [ 19 , 24 ]. Additionally, Gaiser et al found evidence of CD200R-expressing macrophages in Merkel cell carcinoma and suggested a role for the induction of an immunosuppressive M2 phenotype [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While stromal cells express both CD200 and CD200R, future work is underway to more specifically define the immune cell populations that express each protein. CD200R is principally expressed on immune cells of monocyte-macrophage lineage, with an emphasis on myeloid-derived suppressor cells (MDSCs) [ 19 , 24 ]. Additionally, Gaiser et al found evidence of CD200R-expressing macrophages in Merkel cell carcinoma and suggested a role for the induction of an immunosuppressive M2 phenotype [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently published preclinical data illustrated that inhibition of the CD200/CD200R interaction can induce chemokine response, stimulate dendritic cell differentiation, enhance antigen-specific response and ultimately lead to downregulation of PD-1 receptors in glioblastoma multiforme cells [ 29 ]. Additionally, in vivo blockade of this pathway in pancreatic ductal adenocarcinoma animal models significantly reduced intratumoral infiltration and suppressive activity of MDSCs, limited tumor growth, and enhanced the efficacy of PD-1/PD-L1 axis inhibitors [ 24 ]. To our knowledge, our study is the first to assess the correlation between CD200/CD200R and PD-1/PD-L1 pathways in human NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the yes-associated protein (Yap) has been described to contribute to an immunosuppressive tumor microenvironment by inducing the expression and secretion of cytokines and chemokines involved in the differentiation and accumulation of MDSCs [ 63 ]. Within tumor tissue, the expansion of MDSC numbers has been reported to be driven by elevated CD200 expression [ 64 ].…”
Section: Role Of Innate Immune Cells In Pdac: Macrophages and Myelmentioning
confidence: 99%
“…CD200 blockade significantly inhibits tumor growth and diminishes the percentage and number of MDSCs that penetrate in tumor tissue. Similarly, sCD200 present in tumor microenvironment of many cancers extends its effects on MDSCs in the same manner [ 77 , 78 ].…”
Section: Effect Of Cd200 and Cd200r Expression On Function Of Distmentioning
confidence: 99%
“…CD200 is also broadly expressed in other solid tumors, such as pancreatic ductal adenocarcinoma, lung cancer, ovarian cancer, renal cell carcinoma, CNS malignancies and head and neck squamous carcinomas (HNSCC), where its interaction with CD200R(1) promotes immune suppression in tumor microenvironment. The immunosuppressive mechanism promoted by CD200:CD200R interaction relies, as mentioned above, on the inhibition of macrophages, induction of regulatory T cells, switching of cytokine profiles from Th1 to Th2, inhibition of tumor-specific T cell immunity and induction of MDSC (myeloid-derived suppressor cells) expansion [ 77 , 78 , 96 , 98 , 99 ].…”
Section: Importance Of Cd200:cd200r Interactions In Transplantatiomentioning
confidence: 99%